DAMPAK PUNGUTAN PAJAK DILIHAT DARI SEGI HUKUM, EKONOMI DAN SOSIOLOGI - Hamja, Hamja (Yustitia, 2018)
Tax is a mandatory contribution for people who have fulfilled the entry requirements to become taxpayers. The tax is expected to improve the welfare of all people. The tax cannot be felt directly by the community. The implementation of tax collection must have a clear regulation. The purpose of this article is to determine the impact of tax collection in terms of the economy perspective; to know the impact of tax collection if viewed from a legal perspective; to know the impact of tax collection if viewed in terms of sociology. The results of the study indicate that Article 1 of Law Number 6 of 1983 in conjunction with Law 28 of 2007, the definition of tax is a mandatory contribution to the State owed by an individual or entity that is compulsory based on the Law, by not receiving direct compensation and used for State needs for the greatest prosperity of the people. Tax is one of the sources of government revenue. It means that the increase in tax collection directly increases government revenues. Thus, the tax has several functions, namely the function of the budget (budgetair) and the regulating of function (regurelend).